Dynamic pricing optimization for high-speed railway based on passenger flow assignment. - Jiren Cao; Lei Nie; Lu Tong; Zhenhuan He; Zhangjiaxuan Liu (PLoS ONE)
In order to improve the operation efficiency and market competitiveness, how to optimize the ticket pricing strategy of high-speed railway to match the dynamic supply-demand relationship was an urgent problem to be studied. Taking differentiated passenger demand and supply trains as the research object, the space-time service network based on train timetable was constructed. The generalized cost formula and travel utility formula of passenger travel were proposed, which contained economy, rapidity, convenience, comfort, and route correlation cost. A multi-objective dynamic pricing model was proposed. The model aimed at maximize the corporate revenue and maximize passenger travel benefit, and was solved by large neighborhood search heuristic algorithm and path size logit assignment based on capacity constraint-passenger flow increment accurate algorithm. Based on real data, the Shandong circular high-speed railway case compared the average total revenue under different ticket price adjustment ranges and the ticket price for different classes of trains under different OD levels. The case proved the practicability of dynamic pricing adjustment strategy considering train classification, which could provide a reference for the ticket price management of high-speed railway.